Fresh-water algae - Clothier, Geo L. (My University, 1892)
Introduction: This fragmentary treatise upon the Fresh-water Algae of this neighborhood makes no pretense at completeness. It is a nucleus of original investigations about which the author expects to group other facts in future years. In the preparations of this paper, I am greatly indebted to Professor Hitchcock, of the Kansas State Agricultural College, for valuable hints and assistance. To Rev. Francis Nolle of Bethlehem, Pennsylvania, author of “Fresh-Water Algae of the United States”, I owe the acknowledgment of valuable aid through the means of correspondence. Algae are divided according to the coloring matters contained into four classes; namely the Red, or Rhodophyceae; The Olive, or Melanophyceae; the Green, or Chlorophyceae; and the Blue, or Cyanophyceae. The Melanophyceae are found only in salt-water. All my researches have been confined to the Chlorophyceae, although I occasionally had the pleasure of seeing a crawling Oscillaria.
Citation: Clothier, Geo L. Fresh-water algae. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Freshwater algae; Chlorophyceae; Green algae; Botany; Theses; Manuscripts (documents)